Autophagy regulated by day length determines the number of fertile florets in wheat - Ghiglione, H.O. (2008)
The wheat spikelet meristem differentiates into up to 12 floret primordia, but many of them fail to reach the fertile floret stage at anthesis. We combined microarray, biochemical and anatomical studies to investigate floret development in wheat plants grown in the field under short or long days (short days extended with low-fluence light) after all the spikelets had already differentiated. Long days accelerated spike and floret development and greening, and the expression of genes involved in photosynthesis, photoprotection and carbohydrate metabolism. These changes started while the spike was in the light-depleted environment created by the surrounding leaf sheaths. Cell division ceased in the tissues of distal florets, which interrupted their normal developmental progression and initiated autophagy, thus decreasing the number of fertile florets at anthesis. A massive decrease in the expression of genes involved in cell proliferation, a decrease in soluble carbohydrate levels, and an increase in the expression of genes involved in programmed cell death accompanied anatomical signs of cell death, and these effects were stronger under long days. We propose a model in which developmentally generated sugar starvation triggers floret autophagy, and long days intensify these processes due to the increased carbohydrate consumption caused by the accelerated plant development. © 2008 The Authors.